Obtaining Microalgae Biomass Tolerant to Herbicides for Production of Bio-fertilizers: A Review Based on Methodi Ordinatio Methodology - Zanata, Ana Cláudia; Bertan, Fernanda Aparecida Brocco; Bernardi, Caliandra; dos Santos, Casi Santos; Ferreira, Gerusa Albertina; de Oliveira Junior, José Antonio; Fernandes, Maria da Conceição Constantino; Anschau, Andréia (Orbital: The Electronic Journal of Chemistry, 2019)
The objective of this work was to use a systematic review of the literature on the cultivation of microalgae resistant to herbicide using the Method Methodi Ordinatio, which assists the search, selection, collection and classification of scientific articles. Initially, research was done on the databases Scopus, Science Direct and Web of Science, using the keywords “microalgae” and “herbicide”. The results were imported to the Mendeley bibliographic reference manager. Subsequently, the index In Ordinatio index was applied, which works with the three most important factors in a scientific article: The impact factor, the year of publication and the number of citations of the research. This index turns it is possible to classify the most important articles in the area of herbicide-tolerant microalgae and note the importance of this method, which made it possible to find current studies and demonstrate the relevance of this research theme. In order to show the dynamics of the methodology, a research with the theme is presented, comprising works from years 2008 to 2018. The results indicate that the methodology is effective in relation to the objectives proposed, and the most relevant work on the cultivation of herbicide resistant microalgae are used to construct the scenario in this theme.DOI: http://dx.doi.org/10.17807/orbital.v11i6.1244